Aminophylline and progesterone prevent inflammation-induced preterm parturition in the mouse. Issue 4 (11th July 2019) - Herbert, Bronwen R; Markovic, Danijela; Georgiou, Ektoras; Lai, Pei F; Singh, Natasha; Yulia, Angela; Johnson, Mark R
Abstract: Although progesterone (P4) supplementation is the most widely used therapy for the prevention of preterm labor (PTL), reports of its clinical efficacy have been conflicting. We have previously shown that the anti-inflammatory effects of P4 can be enhanced by increasing intracellular cyclic adenosine monophosphate (cAMP) levels in primary human myometrial cells. Here, we have examined whether adding aminophylline (Am), a non-specific phosphodiesterase inhibitor that increases intracellular cAMP levels, to P4 might improve its efficacy using in vivo and in vitro models of PTL. In a mouse model of lipopolysaccharide (LPS)-induced PTL, we found that the combination of P4 and Am delayed the onset of LPS-induced PTL, while the same dose of P4 and Am alone had no effect. Pup survival was not improved by either agent alone or in combination. Myometrial prolabor and inflammatory cytokine gene expression was reduced, but the reduction was similar in P4 and P4/Am treated mice. There was no effect of the combination of P4 and Am on an ex vivo assessment of myometrial contractility. In human myometrial cells and myometrial tissue explants, we found that the combination had marked anti-inflammatory effects, reducing cytokine and COX-2 mRNA and protein levels to a greater extent than either agent alone. These data suggest that the combination of P4 and Am has a more potent anti-inflammatory effect than either agent alone and may be an effective combination in women at high-risk of PTL. Abstract : Summary Sentence The combination of aminophylline and progesterone delays LPS-induced parturition and represses inflammation induced gene expression in myometrial explants and cell cultures